2023
DOI: 10.1002/app.54321
|View full text |Cite
|
Sign up to set email alerts
|

Constructing high‐polarization silica for polyimide‐based nanocomposites with enhanced dielectric permittivity and mechanical performances: Molecular dynamics simulations

Abstract: In this work, the silane coupling agents with 4-carboxyphenyl ( PhCOOH), amino, phenyl, 4-aminophenyl and 4-phenylmethylketone were employed to modify the interfaces of the polyimide/SiO 2 (PIS) nanocomposites, and the effects of the interfacial structures on the dielectric and the mechanical properties for the PI-based composites were predicted by molecular dynamics simulation. The results showed that the interface structure with PhCOOH simultaneously elevated the static dielectric permittivity (ε s ) and You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…The reason may be due to the different restrictions on the dipole moment rotation caused by the dense stacking of molecular chains and strong intermolecular interactions [30]. In addition, density functional theory (DFT) calculations [35,36] and molecular dynamics simulations (MD) [30,[37][38][39] were employed to further understand the relationship between the structure and dielectric properties of PI. A series of model PI molecules with or without a tert-butyl structure were selected.…”
Section: Study Of Dielectric Properties Of Tert-butyl Pi Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason may be due to the different restrictions on the dipole moment rotation caused by the dense stacking of molecular chains and strong intermolecular interactions [30]. In addition, density functional theory (DFT) calculations [35,36] and molecular dynamics simulations (MD) [30,[37][38][39] were employed to further understand the relationship between the structure and dielectric properties of PI. A series of model PI molecules with or without a tert-butyl structure were selected.…”
Section: Study Of Dielectric Properties Of Tert-butyl Pi Filmsmentioning
confidence: 99%
“…Meanwhile, it can be found that the HOMO value of PI with a tert-butyl structure is much higher than that of PI without a tert-butyl structure, indicating that introducing a tert-butyl structure in PI is able to affect the electronic cloud distribution on the diamine and increase the energy of HOMO, thereby reducing the dielectric constant. In addition, density functional theory (DFT) calculations [35,36] and molecular dynamics simulations (MD) [30,[37][38][39] were employed to further understand the relationship between the structure and dielectric properties of PI. A series of model PI molecules with or without a tert-butyl structure were selected.…”
Section: Study Of Dielectric Properties Of Tert-butyl Pi Filmsmentioning
confidence: 99%